The acute effects of caffeine ingestion on reactive agility performance in soccer players - Egesoy, Halit; Yapıcı Öksüzoğlu, Ayşegül (Progress in Nutrition, 2020)
Study Objectives: Caffeine has been shown to provide ergogenic benefits to sports performance. However, limited research is available on the effects of caffeine on agility performance. The study aimed to evaluate the acute effects of caffeine ingestion on reactive agility performance in soccer players. Methods: A total of forty-eight healthy male (age = 16.5 ± 0.5 years, height = 172.3 ± 4.5 cm, body mass = 64.5 ± 5.6 kg, training age: 6.77 ± 1.56 years) youth soccer players volunteered to participate in this study. Participants ingested 6 mg·kg-1 caffeinated coffee (caffeine group) or 6 mg·kg-1 decaffeinated coffee (placebo group) or no coffee (baseline group) with randomized, counter-balanced, single-blind, and repeated-measures experimental design. Movement time (MT), sprint time (ST), total agility time (TAT), and decision time (DT) were analyzed using by one-way repeated-measures ANOVA. Results: There were statistically significant differences among the baseline, caffeine, and placebo conditions on MT (p=0.005), ST (p=0.000), TAT (p=0.000), DT (p=0.000). There were significant differences in MT with caffeine compared with the placebo group (p=0.005). It is seen that the ST value has a significant difference in baseline condition compared to caffeine and placebo group (p=0.000 and p=0.002). There were statistically significant differences between caffeine and baseline status on TAT (p=0.000). There were statistically significant differences between caffeine and baseline condition (p=0.000) and placebo (p=0.000) condition on DT. Conclusion: It can be said that caffeine intake has a positive effect on ST, TAT, and DT components compared to baseline and placebo. Considering the MT values, it is seen that the mean of MT with caffeine is lower than the placebo but higher than the baseline. Caffeine ingestion may supply ergogenic benefit on the reactive agility performance of the soccer players.